Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inlet Flow Field Conditions on the Performance of Centrifugal Compressor Diffusers: Part 2 — Straight-Channel Diffuser

Abstract: This is Part 2 of an examination of influence of inlet flow conditions on the performance and operating range of centrifugal compressor vaned diffusers. The paper describes tests of straight-channel type diffuser, sometimes called a wedge-vane diffuser, and compares the results with those from the discrete-passage diffusers described in Part 1. Effects of diffuser inlet Mach number, flow angle, blockage, and axial flow non-uniformity on diffuser pressure recovery and operating range are addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 2 publications
2
12
1
Order By: Relevance
“…Hence, we can expect the diffuser static pressure recovery to be affected by the flow non-uniformity at impeller exit. Filipenco et al [2000] and Deniz et al [2000] showed that mass-averaged stagnation pressure at diffuser inlet is satisfactory in correlating the diffuser pressure recovery. Based on the above considerations, it is appropriate to express the results on a mass average basis.…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we can expect the diffuser static pressure recovery to be affected by the flow non-uniformity at impeller exit. Filipenco et al [2000] and Deniz et al [2000] showed that mass-averaged stagnation pressure at diffuser inlet is satisfactory in correlating the diffuser pressure recovery. Based on the above considerations, it is appropriate to express the results on a mass average basis.…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
“…Philips [1997], Filipenco et al [2000] and Deniz et al [2000] showed that vaned diffuser channel performance is weakly dependent on inlet blockage, but strongly affected by momentum-averaged flow angle. The three authors used the following definition for the momentum-averaged flow angle:…”
Section: Conceptual Choices For Averaged Resultsmentioning
confidence: 99%
“…The pump model consists of an inlet casing(1), the 7 blades impeller(2), the vaned diffuser(3), having 12 vanes and an annular ring guiding the flow to the discharge pipe (4). The relative gap between the impeller trailing edge and the diffuser leading edge was 5.8%.…”
Section: Experimental Setup Test Pump and Test Loopmentioning
confidence: 99%
“…These flow separations affect negatively the operational behavior of these machines causing reduced efficiency, higher pressure pulsations and increased vibration levels. A variety of numerical and experimental studies on flow separation and unsteady phenomena in centrifugal compressors have been published (Frigne and Van Den Braembussche [1], Haupt et al [2] Filipenco et al [3], Deniz et al [4]), while the number of research publications regarding centrifugal pumps is relatively limited. Hergt and Benner [5] analyzed different diffusers in a free surface test stand at very low rotational speeds.…”
Section: Introductionmentioning
confidence: 99%
“…In a two-part paper, Filipenco and Deniz et al [3,4] argue that radial vaned diffuser pressure recovery performance correlate uniquely to the momentum averaged inflow angle, as long as the pressure recovery coefficient is defined using the "availability average" inflow total pressure. This method of averaging best captures the relevant flow quantities for the diffuser, and under most flow conditions is very similar to the mass flow average [5].…”
Section: Introductionmentioning
confidence: 99%